2019
DOI: 10.1128/mbio.01087-19
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium dentium Fortifies the Intestinal Mucus Layer via Autophagy and Calcium Signaling Pathways

Abstract: Much remains unknown about how the intestinal microbiome interfaces with the protective intestinal mucus layer. Bifidobacterium species colonize the intestinal mucus layer and can modulate mucus production by goblet cells. However, select Bifidobacterium strains can also degrade protective glycans on mucin proteins. We hypothesized that the human-derived species Bifidobacterium dentium would increase intestinal mucus synthesis and expulsion, without extensive degradation of mucin glycans. In silico data reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 199 publications
6
125
0
1
Order By: Relevance
“…Mucin is known as the major component in the intestinal mucus layer, and the intestinal mucosal barrier plays a critical role in maintaining intestinal homeostasis and preventing external damage. Autophagy promotes expression of MUC2 [19,50,51], and OXY induces MUC2 expression in intestinal goblet cells [17]. In this study, we found that OXY activates autophagy and that OXY-induced MUC2 expression is decreased by an ER inhibitor.…”
Section: Discussionsupporting
confidence: 50%
“…Mucin is known as the major component in the intestinal mucus layer, and the intestinal mucosal barrier plays a critical role in maintaining intestinal homeostasis and preventing external damage. Autophagy promotes expression of MUC2 [19,50,51], and OXY induces MUC2 expression in intestinal goblet cells [17]. In this study, we found that OXY activates autophagy and that OXY-induced MUC2 expression is decreased by an ER inhibitor.…”
Section: Discussionsupporting
confidence: 50%
“… 78 Mucin proteins from LS174 T supernatants were collected by ETOH precipitation with protease inhibitors as previously described. 79 MUC2 was purified from crude mucin by guanidinium chloride and cesium chloride gradient ultracentrifugation on a Beckman Coulter Ultra-Centrifuge (30.2 Ti rotor) as previously described. 80 MUC2-containing fractions were identified by slot blot immunostaining with a MUC2 antibody (cat# NBP1-31231, 1:100 dilution, Novus), LI-COR Odyssey Blotting reagents, Odyssey imaging system, and Image Studio software (LI-CORE Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…This is because the attack of most pathogens is blocked by glycosylated proteins covering the host cell surface as barriers. Such barriers may act in two manners in host defense, (I) physically separate pathogens and host cells [75,76]; (II) chemically inhibit or kill pathogens [16,[77][78][79].…”
Section: Glycosylated Proteins Of Hosts Act As Barriers To Defense Pamentioning
confidence: 99%